2004
DOI: 10.1038/sj.bjc.6601641
|View full text |Cite
|
Sign up to set email alerts
|

Rounding of low serum creatinine levels and consequent impact on accuracy of bedside estimates of renal function in cancer patients

Abstract: To compare glomerular filtration rate measured by technetium-99m ([Tc 99m ]) DTPA clearance with estimated creatinine clearance (CrCl) (Cockcroft and Gault (C&G) method) in patients with serum creatinine (Scr) levels o0.06 mmol l À1 , and determine the effect of rounding serum creatinine to 0.06 mmol l À1 . Patients with serum creatinine values o0.06 mmol l À1 at the time of [Tc 99m ] clearance determination were identified. Creatinine clearance was calculated by the C&G method using both actual and rounde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…Pharmacists often “round” Scr values to an arbitrary threshold value in older patients or those with low Scr values to account for low muscle mass. This practice is inaccurate and may lead to drug dosing errors in certain populations [1316]. Currently, KDIGO guidelines on drug dosing advocate using either Cockcroft Gault or MDRD equation for drug dosing [17].…”
Section: Riskmentioning
confidence: 99%
“…Pharmacists often “round” Scr values to an arbitrary threshold value in older patients or those with low Scr values to account for low muscle mass. This practice is inaccurate and may lead to drug dosing errors in certain populations [1316]. Currently, KDIGO guidelines on drug dosing advocate using either Cockcroft Gault or MDRD equation for drug dosing [17].…”
Section: Riskmentioning
confidence: 99%
“…The National Kidney Disease Education Program (NKDEP) recently recommended that eGFR (MDRD equation) and the CG equation can be used interchangeably for the purpose of drug dosing, a recommendation that is controversial and has not been rigorously evaluated in older patients. In older individuals with very low S cr values (less than 1.0 mg/dl) and reduced muscle mass, a common practice of replacing S cr with an arbitrary value, such as 1.0 mg/dl, for use in the CG equation has been reported but not fully evaluated …”
mentioning
confidence: 99%
“…Although the C‐G equation has not definitively been shown to provide a better estimate of renal function than the MDRD or CKD‐EPI equations, it is used more frequently because most drug trials and the majority of drug package inserts use the C‐G equation to estimate renal function and formulate dosing recommendations . Recently, some package inserts have incorporated dosing recommendations using GFR values, and several respondents indicated that they do utilize the MDRD equation in clinical practice. This is consistent with national recommendations as the Kidney Disease: Improving Global Outcomes (KDIGO) guidelines advocate using either the MDRD or the C‐G equation for drug dosing purposes …”
Section: Discussionmentioning
confidence: 99%